Menciptakan Karakter yang Menarik dalam Penulisan Naskah Film - Sasongko, Hario (Bina Nusantara University, 2013)
The main character in a movie is the central to the film itself. Generally, a movie tells the story of a specific character. The character can be drawn from figures that exist in the real world or a fictional character. Thus, the success of a movie is always directly proportional to the success of a movie script writer in formulating the main character in the movie. By the increasing of techniques of writing a story, it can be determined how to make characters to be interesting in a movie script.